On media violence - Potter, W. James (Sage Publications, 1999)
"On Media Violence is a definitive examination of this hotly debated social topic. Media scholar W. James Potter asks provocative questions such as: How much media violence is there? What are the meanings conveyed in the way violence is portrayed? What effect does it have on viewers individually, as members of particular groups, and as members of society?" "On Media Violence is essential reading for students and scholars of media studies, communication theory, popular culture, social psychology, and sociology."--Jacket.